VARIABILITAS SIFAT KIMIA KAYU BULAN DAN MAHANG BERDASARKAN ARAH AKSIAL : John F. Gustaf, I.Nyoman Surasana dan Gimson Luhan - Admin JHT (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2017)
ABSTRACT Wood of moon (Fagraea crenulata) and wood of mahang (Macaranga sp.) are not included the commercial timber species, therefore the knowledge regarding chemical properties of their woods are needed in order to provide information for various purposes according to their properties. The research was aimed to know chemical properties of moon wood and mahang wood. The research had been conducted at the laboratory of Forestry Department, University of Palangka Raya since February to March 2017. Research resultd showed that the solubility of moon and mahang woods in the cold water, hot water, 1% NaOH and alcohol benzene are classified as high. According chemical components analysis, their wood are not suitable for pul and paper, because they have some characteristic as follow: holoselulosa is poor, cellulose is low, hemicellulose is middle, and lignin is not good. Meanwhile, wood ash of moon and mahang are classified moderate (range of Indonesia chemical components of broadleaf wood is range start from 0.2 to 6%) with values of them are 0.654% for moon wood and 0.689% for mahang wood. With the result their woods are considered to wood energy utilization. Keywords: chemical component, mahang wood, moon wood, wood energy